Multicultural Education as a Strategy for Maintaining Unity and harmony in diversity in North Lombok Regency - Najib, Muhammad; Suprapto, Suprapto; Khusniyah, Nurul Lailatul; Thoib, Ismail (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2025)
North Lombok Regency is a region characterised by ethnic, religious, and cultural diversity. This sociocultural reality demands an educational system that fosters tolerance, multiple identities, and social cohesion. This study explores the implementation of the Back to the Essence of Education Movement (GKKP) as a model of multicultural education based on locality. This study employs a qualitative approach with thematic content analysis of relevant educational policy documents, such as strategic plans, local curriculum content, character education enhancement guidelines, and annual GKKP program reports. Data were analysed based on Banks' five dimensions of multicultural education and Paulo Freire's principles of critical pedagogy. Validity is ensured through triangulation of sources and peer debriefing. Findings indicate that the GKKP integrates religious and local cultural values into intraschool and extracurricular learning. Using skill-building pocketbooks enables the structured internalisation of multicultural values, covering spiritual, national, school environment, and self-development aspects. The program also fosters an inclusive, collaborative, and democratic school culture and encourages the formation of dual identities among students as members of the local community and citizens of Indonesia. The GKKP model significantly contributes to developing a culturally relevant, localised, multicultural education approach. Despite challenges such as limited teacher training and local teaching materials, this initiative is a viable alternative to the dominance of Western-based multiculturalism approaches in educational literature.